The Association of Clean and Healthy Lifestyle Behaviors and Nutrient Intake With The Nutritional Status of Adolescents - Sulistiawati, Febrina; Baiq Dewi Sukma Septiani; Romy Hidayat; Wijanarko, Mutiara Arsya Vidianinggar (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Adolescents represent a population group that is particularly vulnerable to various nutritional issues, including both undernutrition and overnutrition. With the rising number of adolescents in Indonesia, adolescent nutrition has become a public health concern due to its significant implications for physical growth and development, as well as its long-term impact on nutritional status into adulthood and later life. This research explored the association between Clean and Healthy Lifestyle Behaviors (CHLB) and dietary intake, with a focus on their impact on the nutritional status of adolescents. Utilizing a cross-sectional design, the study was conducted at SMPN 18 Mataram and included 60 student participants. Data were analyzed through Spearman’s rank-order correlation test. Findings indicated a significant correlation between CHLB and adolescents’ nutritional status (p=0.001, p<0.05). Similarly, macronutrient intake, including carbohydrates, proteins, and fats, was significantly related to nutritional status, with p-values of 0.000, 0.005, and 0.001, respectively (p<0.05). In contrast, no significant relationship was found between micronutrient intake (vitamin C and iron) and nutritional status, with p-values of 0.315 and 0.352, respectively (p>0.05). These findings suggest the need to enhance adolescents’ awareness and practices regarding clean and healthy lifestyle behaviors and to encourage the adequate consumption of both macro- and micronutrients in order to support optimal nutritional status.